An Ultrasonic Transmission/Reflection Mode Tomography for Two-Phase Flow Measurement - Omid Qorbani; Esmaeil Najafiaghdam (International Journal of Industrial Electronics, Control and Optimization, 2022)
Ultrasonic process tomography obtains the distribution of the two-phase flow based on ultrasound propagation in different fluids, thus is valuable to industrial monitoring and measurement. Ultrasonic process tomography can do a non-intrusively exploration of the multi-phase flow hydrodynamics. In this paper, a dual-mode ultrasonic process tomography is presented that fuses by reflection-mode tomography and time-of-flight ultrasonic tomography. In this method, a 32-digit array of ultrasonic sensors have been used for flow measurement. The two-phase flow rate that involves liquid and gas phases, have been calculated through a simple algebraic algorithm with obtained data from sensors. Simulation results depict that the measurement technique is independent of the fluid flow pattern and the system error also has been decreased. The invention of the article is about a simple algebraic method for image reconstruction which a special case is not considered in it and simultaneously, the image reconstruction error has been reduced. The relative error of the reconstructed images is presented by MATLAB simulation and it is much lower than the conventional methods. For a gas bubble with ultrasonic wave reflection time from its surface, the simulation results depict the SIE factor is less than 2%.